Thrombin-activatable fibrinolysis inhibitor (TAFI) deficiency is compatible with murine life - Nagashima, Mariko (American Society for Clinical Investigation, 2002)
To investigate the consequence of deficiency in thrombin-activatable fibrinolysis inhibitor (TAFI), we generated homozygous TAFI-deficient mice by targeted gene disruption. Intercrossing of heterozygous TAFI mice produced offspring in the expected Mendelian ratio, indicating that transmission of the mutant TAFI allele did not lead to embryonic lethality. TAFI-deficient mice developed normally, reached adulthood, and were fertile. No gross physical abnormalities were observed up to 24 months of age. Hematological analysis of TAFI-deficient mice did not show any major differences including plasma fibrinogen level, prothrombin time, and activated partial thromboplastin time. TAFI-deficient mice did not suffer from excess bleeding as determined by blood loss following tail transection, although their plasma failed to prolong clot lysis time in vitro. In vivo, TAFI deficiency did not influence occlusion time in either an arterial or a venous injury model. TAFI deficiency did not improve survival rate compared with the wild-type in thrombin-induced thromboembolism, factor X coagulant protein–induced thrombosis, and endotoxin-induced disseminated intravascular coagulation. Furthermore, TAFI deficiency did not alter kaolin-induced writhing response, implying that TAFI does not play a major role in bradykinin catabolism. The current study demonstrates that TAFI deficiency does not change normal responses to acute challenges.